AKTIVITAS KOMUNIKASI PENYULUH PERIKANAN DALAM PEMBERDAYAAN MASYARAKAT PETAMBAK DI DESA PARIA KECAMATAN DUAMPANUA KABUPATEN PINRANG - Annisa Ansar , Nurul; Majid , Abdul; Zelfia, Zelfia (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
This study aims to describe the communication process of fishery instructors in community empowerment and the development of the farmer community in Paria Village, Duampanua District, Pinrang Regency. This study used descriptive qualitative method. Descriptive qualitative technique is a research method that utilizes qualitative data and is described descriptively. Data collection is the technique of observation, interviews and documentation. Data analysis was carried out by collecting data, reducing, presenting data and drawing conclusions. The results showed that in answering the formulation of the problem discussed in this study, the communication of fishery instructors in empowering the farmer community in Paria village, Patampanua subdistrict was able to make a major contribution to the farmer community, namely by providing assistance with tools/materials in order to support the success of the harvest. Through the provision of tools, seed assistance, as well as the training provided can improve good cultivation skills for the farmer community.